Multicentric Bone Lesions Due to Parathyroid Disease: A Case Report - Gilligan DDS, Gerardo; Moine DDS, Lorena; Ferreyra DDS, PhD, Ruth; Panico DDS, PhD, René (Odovtos - International Journal of Dental Sciences, 2017)
Introduction: Hyperparathyroidism is an endocrine disorder that could create parathyroid hormone hypersecretion conditions, propitious for bone tumors development. Although is not frequent, maxillary bones may be involved in the pathogenesis of these lesions. PATIENTS AND METHODS: In this case, a 56-year-old female is reported. An Hyperparathyroidism was diagnosed due to multiple maxillary and extra-maxillary multicentric bone lesions, with a predominance of giant cells, linked to her endocrine disorder. Discussion: The diagnosis of a Hyperparathyroidism Brown Tumor must meet serological, clinical and histopathological criteria. The multifocality of the lesions is the most remarkable clinical aspect in this case. For an adequate treatment of this entity is necessary an interdisciplinary and coordinate work between different areas of healthcare physicians and Oral Medicine specialist.